Environmental risk factors for the incidence of cutaneous leishmaniasis in an endemic area of Iran: A GIS-based approach. (June 2017) - Ramezankhani, Roghieh; Hosseini, Arezoo; Sajjadi, Nooshin; Khoshabi, Mostafa; Ramezankhani, Azra
Highlights: This study shows cutaneous leishmaniasis (CL) has been increasing in Isfahan. CL cases in the Isfahan province was significantly clustered across 23 counties. GWR provided a better fit to the data compared with OLS. GWR revealed local variations in relationships relevant to environmental factors. Temperature and population density had positive association with CL incidence. Abstract: Objectives: This study was designed to determine the environmental factors associated with cutaneous leishmaniasis (CL) in Isfahan Province, using spatial analysis. Methods: Data of monthly CL incidence from 2010 to 2013, climate and environmental factors including: temperature, humidity, rainfall, wind speed, normalized difference vegetation index (NDVI), altitude and population density across the Isfahan's cities was used to perform spatial analysis by ordinary least square (OLS) regression and geographically weighted regression (GWR). Results: OLS revealed a significant correlation between CL incidence and five predictors including temperature, population density, wind speed, humidity and NDVI; which explained 28.6% of variation in CL incidence in the province. Considering AICc and adjusted R 2, GWR provided a better fit to the data compared with OLS. Conclusion: There was a positive correlation between temperature and population density with CL incidence in both local (city) and global (province) level.